To add five species of Cyclopidae (Cyclopoida - Copepoda) to the fauna of freshwater zooplankton of Vietnam - Luong, Tran Duc; Hai, Ho Thanh (Academia Journal of Biology, 2014)
In Vietnam, according to Dang Ngoc Thanh et al. 1980, Ho Thanh Hai et al. 2007, 11 species belonging to seven genus Eucyclops, Paracyclops, Ectocyclops, Tropocyclops, Mesocyclops, Thermocyclops, Microcyclops and Halicyclops are recorded in fresh waters of Vietnam. Based on analysis of many samples collected from various waters in Vietnam during 2002-2008, five species belonging to Cyclopidae including Macrocyclops albidus, Paracyclops affinis, Eucyclops euacanthus, Tropocyclops candidiusi, and Tropocyclops bopingi that are firstly found in Vietnam. All of these species are described in detail in the paper. Typical characters on taxonomy are used for identification of species such as: structure of antennule, shape of receptaculum seminis (R.S.), armature of connecting plate, coxopodite and basipodite of P4, the third segment of endopodite of P4 (Enp3 P4), leg 5, the proportion of the terminal spines of Enp3 P4, the spines formula of exopodite of P1-P4, and of the caudal ramie, relative length of caudal setae. Macrocyclops albidus and Paracyclops affinis are cosmopolite species. Eucyclops euacanthus was recorded in Asean, China and India. The Tropocyclops candidiusi was described first time from Taiwan (China) by Harada (1931), Tropocyclops bopingi was firstly described from Guangdong (China) by Dumont (2006), that widely distributed in south China Up to now, 16 species belonging to 7 genera of Cyclopidae-Cyclopoida are recorded in fresh waters of Vietnam. The amount of species of Cyclopidae of Vietnam can be surely increased, when genera Microcyclops, Thermocyclops and Mesocyclops should be revised in species composition.